20-YEAR COOPERATION WITH IGIP - Alexander N. Solovyev (Высшее образование в России)
The article highlights the milestones of the history of cooperation between MADI and the International Society for Engineering Education IGIP, analyzes the ways of integration of Russian engineering education into the global education area. Moscow Automobile and Road Constructing State Technical University (MADI) has played a significant role in engineering pedagogy formation in Russia. IGIP Russian Monitoring Committee based upon MADI contributed greatly to the creation of the network of IGIP certified centers for engineering pedagogy and the development of international integration of engineering education.